We hope for better things - Bartels, Erin, 1980- (Thorndike, Maine : Center Point Large Print, 2019)
"A disgraced journalist moves into her great-aunt's secret-laden farmhouse and discovers that the women in her family were testaments to true love and courage in the face of war, persecution, and racism as readers are taken on an emotional journey through time from the volatile streets of 1960s Detroit to the Underground Railroad during the Civil War"--
Keywords: Journalistic ethics; Civil rights; Domestic fiction; Family secrets; African Americans; Large type books; War fiction